2008
DOI: 10.1021/jf073065v
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon Bark Proanthocyanidins as Reactive Carbonyl Scavengers To Prevent the Formation of Advanced Glycation Endproducts

Abstract: Cinnamon bark has been reported to be effective in the alleviation of diabetes through its antioxidant and insulin-potentiating activities. In this study, the inhibitory effect of cinnamon bark on the formation of advanced glycation endproducts (AGEs) was investigated in a bovine serum albumin (BSA)-glucose model. Several phenolic compounds, such as catechin, epicatechin, and procyanidin B2, and phenol polymers were identified from the subfractions of aqueous cinnamon extract. These compounds showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(178 citation statements)
references
References 25 publications
(27 reference statements)
5
167
0
6
Order By: Relevance
“…Multidisciplinary studies have demonstrated that the composition of a polyphenol has an outstanding relationship to its antioxidant properties. On the other hand, the antioxidant activity of a natural compound shows strong linking with its molecular structures [45]. Therefore, it is an important matter to assess the antioxidant activity of a polyphenolic compound not only quantity but also by quality (which is decided by chemical structure).…”
Section: Diabetic Wound Healingmentioning
confidence: 99%
See 3 more Smart Citations
“…Multidisciplinary studies have demonstrated that the composition of a polyphenol has an outstanding relationship to its antioxidant properties. On the other hand, the antioxidant activity of a natural compound shows strong linking with its molecular structures [45]. Therefore, it is an important matter to assess the antioxidant activity of a polyphenolic compound not only quantity but also by quality (which is decided by chemical structure).…”
Section: Diabetic Wound Healingmentioning
confidence: 99%
“…Mimicking insulin activity [45] Curcuma longa (Turmeric) Curcumin Preventing free radicals and glycosylated haemoglobin (HbA) formation, protecting non-enzymatic antioxidants pools, preventing of lipid peroxidation, lowering blood glucose level [59,61,62,66] Cyperus rotundus (Nut sedge) Gallic acid, p-coumaric acid, epicatechin Reduction of protein carbonyl and thiol oxidation…”
Section: Plantmentioning
confidence: 99%
See 2 more Smart Citations
“…Catechin and epicatechin procyanidin B2 (a dimer-type proanthocyanidin) isolated from cinnamon bark extract have been shown to possess a significant MGO trapping activitiy, with procyanidin B2 demonstrating the strongest inhibition of AGE formation among proanthocyanidins isolated from cinnamon bark [146]. All these flavonoids potently inhibited (more than 50%) the formation of pentosidine and CML [147] with procyanidin B2 showing the highest inhibition capacity (almost 80%) on the CML formation.…”
Section: The Most Important Catechins Of Green Tea Are (-)-Epicatechimentioning
confidence: 99%